Pseudoprogression in children, adolescents and young adults with non-brainstem high grade glioma and diffuse intrinsic pontine glioma - Carceller, Fernando; Jones, David T. W.; Hovestadt, Volker; Pfister, Stefan (Journal of neuro-oncology, 2016)
Pseudoprogression (PsP) is a treatment-related phenomenon which hinders response interpretation. Its prevalence and clinical impact have not been evaluated in children/adolescents. We assessed the characteristics, risk factors and prognosis of PsP in children/adolescents and young-adults diagnosed with non-brainstem high grade gliomas (HGG) and diffuse intrinsic pontine gliomas (DIPG). Patients aged 1-21 years diagnosed with HGG or DIPG between 1995 and 2012 who had completed radiotherapy were eligible. PsP was assessed according to study-specific criteria and correlated with first-line treatment, molecular biomarkers and survival. Ninety-one patients (47 HGG, 44 DIPG) were evaluable. Median age: 10 years (range, 2-20). Eleven episodes of PsP were observed in 10 patients (4 HGG, 6 DIPG). Rates of PsP: 8.5 % (HGG); 13.6 % (DIPG). Two episodes of PsP were based on clinical findings alone; nine episodes had concurrent radiological changes: increased size of lesions (n = 5), new focal enhancement (n = 4). Temozolomide, MGMT methylation or H3F3A mutations were not found to be associated with increased occurrence of PsP. For HGG, 1-year progression-free survival (PFS) was 41.9 % no-PsP versus 100 % PsP (p = 0.041); differences in 1-year overall survival (OS) were not significant. For DIPG, differences in 1-year PFS and OS were not statistically significant. Hazard ratio (95 %CI) of PsP for OS was 0.551 (0.168-1.803; p = 0.325) in HGG; and 0.308 (0.107-0.882; p = 0.028) in DIPG. PsP occurred in both pediatric HGG and DIPG patients at a comparable rate to adult HGG. PsP was associated with improved 1-yr PFS in HGG patients. PsP had a protective effect upon OS in DIPG patients.